1994
DOI: 10.1104/pp.105.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Chilling Injury Induces Lipid Phase Changes in Membranes of Tomato Fruit

Abstract: Wide-angle x-ray diffraction has provided evidence for lipid phase separations in microsomal membranes from chill-injured tomato (Lycopersicon esculentum Mill. cv Caruso) fruit. Maturegreen fruit stored for 20 d at 5'C had not begun to ripen and were essentially free of chilling injury symptoms. Within 4 d of being returned to 25"C, however, the fruit displayed characteristic symptoms of chilling injury, including translucent water-soaked patches, surface pitting, and irregular pigmentation. Membrane damage me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 2 publications
5
51
0
3
Order By: Relevance
“…DHS-suppressed fruit also exhibited a delay in the onset of electrolyte leakage associated with fruit senescence. Electrolyte leakage is a well-established trait of senescing tissues and is thought to reflect lipid phase changes attributable to enhanced lipase activity and ensuing leakiness of membrane bilayers (Eze et al, 1986;Sharom et al, 1994). Electrolyte leakage for transgenic fruit at 40 d postbreaker was the same as that for wild-type fruit at 20 d postbreaker, confirming a very significant delay in senescence and spoilage of the transgenic fruit.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…DHS-suppressed fruit also exhibited a delay in the onset of electrolyte leakage associated with fruit senescence. Electrolyte leakage is a well-established trait of senescing tissues and is thought to reflect lipid phase changes attributable to enhanced lipase activity and ensuing leakiness of membrane bilayers (Eze et al, 1986;Sharom et al, 1994). Electrolyte leakage for transgenic fruit at 40 d postbreaker was the same as that for wild-type fruit at 20 d postbreaker, confirming a very significant delay in senescence and spoilage of the transgenic fruit.…”
Section: Discussionsupporting
confidence: 55%
“…Fruits were peeled at the location of measurement due to the resistance of the skin, and firmness was taken to be the amount of pressure required to puncture the surface of the exposed fruit pulp. Electrolyte leakage of pericarp discs from fruit at selected stages of postharvest development was measured at room temperature over a 3-h period using a conductance meter (model 1056; Amber Science, Eugene, OR) as described previously (Sharom et al, 1994).…”
Section: Postharvest Fruit Storage Firmness and Electrolyte Leakagementioning
confidence: 99%
See 1 more Smart Citation
“…1; CI symptoms in cold-stored bananas. Chilling injury is thought to result in increased membrane permeability leading to an increase in leakage of cellular constituents (Murata, 1990;Sharom et al, 1994). The rate of ion leakage from excised tissue into an isotonic aqueous solution is a useful measure of the severity of chilling-induced increase in membrane permeability (King & Ludford, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there are likely other membrane qualities that contribute to the sensitivity of the membrane to low temperature. Sharom et al (1994) have even contested the idea that low temperature directly causes the phase change and have suggested that it is the result of biochemical events occurring during rewarming. Although it is clear that low temperature affects the function of membranes and membraneassociated proteins and that a phase change is associated with chilling injury, there remains much to be discovered about the mechanism by which low temperature affects membrane function and about the qualities of the membranes that are important for chilling tolerance.…”
Section: Effects Of Chilling On Plant Metabolismmentioning
confidence: 99%